Learning about Theories of Change for the Monitoring and Evaluation of Research Uptake - Barnett, Chris; Gregorowski, Robbie (IDS, 2013)
This paper captures lessons from recent experiences on using ‘theories of change’ amongst organisations involved in the research–policy inte rface. The literature in this area highlights much of the complexity i nherent in the policymaking process, as well as the challenges around finding meaningful ways to measure research uptake. As a tool, ‘theori es of change’ offers much, but the paper argues that the very complexi ty and dynamism of the research-to-policy process means that any theor y of change will be inadequate in this context. Therefore, rather than overcomplicating a static depiction of change at the start (to be eva luated at the end), incentives need to be in place to regularly collec t evidence around the theory, test it periodically, and then reflect a nd reconsider its relevance and assumptions.